2021
DOI: 10.2147/dddt.s310481
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Effect and Mechanism of Fructus Lycii, Rehmanniae Radix Praeparata, and Paeonia lactiflora in the Treatment of AMD Based on Network Pharmacology and in vitro Experimental Verification

Abstract: Purpose The aim of this study was to observe the mechanism of Fructus Lycii (FL), Rehmanniae Radix Praeparata (RRP) and Paeonia lactiflora (PL) in treating age-related macular degeneration (AMD) based on network pharmacology and biological experiments. Methods Bioactive compounds, potential targets of FL, RRP and PL, and genes related to AMD, were acquired from public databases. Functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…SHSY-5Y cells pretreated with trans-ferulic acid were able to alleviate cell death caused by H 2 O 2 -induced toxicity as well as decreased ROS level and apoptotic cells (Gay et al, 2018). The pretreatment of ARPE-19 cells with SDH significantly increased cell viability, decreased intracellular ROS levels, and induced cell apoptosis by H 2 O 2 (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…SHSY-5Y cells pretreated with trans-ferulic acid were able to alleviate cell death caused by H 2 O 2 -induced toxicity as well as decreased ROS level and apoptotic cells (Gay et al, 2018). The pretreatment of ARPE-19 cells with SDH significantly increased cell viability, decreased intracellular ROS levels, and induced cell apoptosis by H 2 O 2 (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 92%
“…SHSY‐5Y cells pretreated with trans‐ferulic acid were able to alleviate cell death caused by H 2 O 2 ‐induced toxicity as well as decreased ROS level and apoptotic cells (Gay et al, 2018). The pretreatment of ARPE‐19 cells with SDH significantly increased cell viability, decreased intracellular ROS levels, and induced cell apoptosis by H 2 O 2 (Chen et al, 2021). Catalpol, an active component of SDH, had neuroprotective properties and improvement in learning and memory disorders by elevating brain‐derived neurotrophic factor and attenuating neuronal apoptosis and energy metabolism failure (Yuan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 can be found in the cytoplasm as a dimer formed with Kelch-like ECH-associated protein 1 (Keap1), however, when subjected to stimuli such as oxidative stress, it will dissociate from Keap1 and transferred to the nucleus where it binds to ARE, and regulate the expression of ARE-mediated phase II detoxi cation and antioxidant enzymes, including heme oxygenase-1 (HO-1), glutamate-Cysteine ligase (GCL) and NAD(P)H: quinone oxidoreductase (NQO1) (9), among which, HO-1 showed to be an important antioxidant enzyme that reduces cell damage (10). The upregulation of Nrf2 protects retinal cells from oxidative damage and rescues the function of the retina (11)(12)(13) Recent studies have demonstrated, the Nrf2/HO-1 signaling pathway can be activated by abundant bioactive compounds from natural products to regulate the traumatic and stressed status of the retina (14).…”
Section: Introductionmentioning
confidence: 99%
“…According to TCM theory, the MMDH pill contains 11 herbs, possessing the functions of nourishing the kidney, calming the liver, and improving eyesight. Our previous study indicated that Fructus lycii, Rehmanniae Radix Praeparata, and Paeonia lactiflora (the main three herbs of the MMDH pill) reduce H 2 O 2 -induced oxidative stress and apoptosis in RPE cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%